2022
DOI: 10.1596/1813-9450-10198
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Global Inequality and Poverty

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 38 publications
2
59
0
2
Order By: Relevance
“…It led to cancelation of political, religious, and cultural events and of in-person work for much of the earth’s population. The International Labor Organization predicts a 6.7% loss of job hours globally in the second quarter of 2020, equivalent to 195 million full-time jobs (Mahler, Lakner, Aguilar, & Wu, 2020). Schools and universities closed for at least some of the duration in 172 countries, affecting 98.5% of the world’s students (UNESCO, 2020).…”
mentioning
confidence: 99%
“…It led to cancelation of political, religious, and cultural events and of in-person work for much of the earth’s population. The International Labor Organization predicts a 6.7% loss of job hours globally in the second quarter of 2020, equivalent to 195 million full-time jobs (Mahler, Lakner, Aguilar, & Wu, 2020). Schools and universities closed for at least some of the duration in 172 countries, affecting 98.5% of the world’s students (UNESCO, 2020).…”
mentioning
confidence: 99%
“…The World Bank reported that 734 million people lived with extreme poverty (less than $1.90 a day) in 2015. In view of COVID-19, an additional 40 to 60 million people are likely to be trapped in extreme poverty (Mahler et al, 2020). The COVID-19 pandemic forced not only 1.12 billion people into extreme poverty worldwide but also millions of people in above poverty line are also likely to suffer from extreme poverty due to lack of social security.…”
Section: Povertymentioning
confidence: 99%
“…The procedures to estimate the impact of the pandemic on poverty in Africa are the following (see also, Mahler et al, 2022): first, to project household surveys to 2020, we need distribution of welfare (income or consumption) in 2019 for all countries. However, household surveys are not conducted annually in most low and middle-income countries.…”
Section: Impact Of Covid-19 On Povertymentioning
confidence: 99%
“…5 Then, using the same extrapolation method, we extrapolate the 2019 country distributions forward to 2020 and 2021. Following Mahler et al (2022), we report two different scenarios projecting poverty for the COVID-19 affected years: (i) a series incorporating the effect of the pandemic ("with COVID-19"), and (ii) one without the effect of the pandemic ("without COVID-19"). The former uses the per capita GDP growth rates from the World Bank's June-2021 Global Economic Prospects (GEP) report, while the latter uses January-2020 GEP forecasts -that is growth forecasted before the pandemic and thus not incorporating the effects of the pandemic.…”
Section: Impact Of Covid-19 On Povertymentioning
confidence: 99%